Changes in 5-HT4 receptor and 5-HT transporter binding in olfactory bulbectomized and glucocorticoid receptor heterozygous mice - Licht, Cecilie; Kirkegaard, Lisbeth; Zueger, Maha; Chourbaji, Sabine; Gass, Peter; Aznar, Susana; Knudsen, Gitte M. (Neurochemistry international, 2010)
The 5-HT4 receptor is a new potential target for antidepressant treatment and may be implicated in the pathogenesis of depression. This study investigated differences in 5-HT4 receptor and 5-HT transporter (5-HTT) binding by quantitative autoradiography of [3H]SB207145 and (S)-[N-methyl-3H]citalopram in two murine models of depression-related states, olfactory bulbectomy and glucocorticoid receptor heterozygous (GR+/−) mice. The olfactory bulbectomy model is characterized by 5-HT system changes, while the GR+/− mice have a deficit in hypothalamic-pituitary-adrenal (HPA) system control. The olfactory bulbectomized mice displayed increased activity in the open field test, a characteristic depression-like feature of this model. After bulbectomy, 5-HT4 receptor binding was increased in the ventral hippocampus (12%) but unchanged in the dorsal hippocampus, frontal and caudal caudate putamen. Among post hoc analyzed regions, there was a 14% decrease in 5-HT4 receptor binding in the olfactory tubercles. The 5-HTT binding was unchanged in the hippocampus and caudate putamen of bulbectomized mice but post hoc analysis showed small decreases in lateral septum and lateral globus pallidus. In comparison, GR+/− mice had increased 5-HT4 receptor (11%) binding in the caudal caudate putamen and decreased 5-HTT binding in the frontal caudate putamen but no changes in dorsal and ventral hippocampus. Post hoc analysis showed increased 5-HT4 receptor binding in the olfactory tubercles of GR+/− mice. In conclusion, we have found brain regional changes in 5-HT4 receptor and 5-HTT transporter binding in two murine models of depression-related states, characterized by 5-HT and HPA system changes.
Gesehen am 14.03.2023
Im Titel ist die Zahl 4 tiefgestellt